PINJAMAN DANA DARI TIONGKOK KE SRI LANKA UNTUK PEMBANGUNAN PELABUHAN HAMBANTOTA DI SRI LANKA - Athariq Dwi Awaly; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Belt and Road Initiative (BRI) is one of the strategies developed by China under the government of Xi Jinping in 2013. Belt and Road itself is business economy, diplomatic, And geopolitics multifaceted. Objective from held this policy is to link the economies of Eurasia, East Africa, Europe and more than 71 countries. Sri Lanka is one of China's target countries in implementing this strategy. China has carried out various relations in Sri Lanka such as cooperation, investment. Therefore, the researcher drew the question